TRANSLATING WEBTOON’S SOUND EFFECTS: A CASE OF INSTANTMISO’S SIREN’S LAMENT - Dinda Nur Puspitasari (UIN Raden Mas Said Surakarta, 2022)
The aim of this research is to analyze sound effect translation. The objectives of this research are; to describe the categories of sound effect on web comics Siren’s Lament, and to reveal comic translation strategies to translate sound effect on web comics Siren’s Lament. The data are taken from instantmiso’s (pen name) web comics entitled Siren’s Lament season 1 and season 2 in English and Indonesian version which can be found on Webtoon. Observation and documentation are techniques of collecting data used in this research. For technique of analyzing data, the researcher used the theory of Spradley (1979), involving domain, taxonomy, componential table, and finding cultural themes. Among 99 data found in the analysis, some categories are obtained. Those categories of sound effect were; Impact (26 data (26.3%)), Friction (11 data (11.1%)), Air Current (23 data (23.2%)), Sound involving Liquid and Food (17 data (17.2%)), Breakage (3 data (3.0%)), Explosion and Gunshot (1 data (1.0%)), Sound with Long Duration (13 data (13.1%)), and Pitch (5 data (5.1%)). The dominant data of sound effect category is Impact with 26 data. In terms of strategies, the results showed that 70 data applied repetition strategy, 2 data applied translation strategy, 80 data applied Substitution strategy, and 1 data applied Deletion strategy. Substitution becomes dominant strategy and shows that the translator does not change the overall meaning, but only translates the sound effect into a typical sound in Indonesia.